“Integrating Visual Arts in Education: Enhancing Creativity and Cognitive Skills from Schools to Universities” - Aslonova Shaxnoza Islom qizi (INTERNATIONAL JOURNAL OF SCIENCE-INNOVATIVE RESEARCH, 2025)
Abstract: This article investigates the role of visual arts in enhancing students’ creativity and cognitive abilities in school and university education. It emphasizes how early exposure to visual arts supports skill development, imaginative thinking, and problem-solving. Furthermore, higher education builds upon these foundations through advanced projects, interdisciplinary learning, and professional training. The study highlights the necessity of integrating visual arts across educational levels to foster holistic development and prepare students for creative professions.